Complaints Strategies used by Guest and Employees at Kashantee Village Hotel - I Nyoman Rai Martika Giri; Ni Putu Cahyani Putri Utami (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This research was conducted using a qualitative descriptive method whose data source came from conversations between hotel guests and employees at the Kashantee Village Hotel. Where the data were analyzed using theory from Austin (1962) to analyze the Locutionary, Illocutionary and Perlocutionary Actfrom the complaint strategy found. The author found that there were four complaint strategies found in Kashantee Village Hotel, namely No Explicit Blame, Blame, Repair Request, Threat. and the writer hopes that the readers can understand how the strategy for resolving hotel guest complaints is based on speech acts.